Posibilidades para la agricultura regenerativa en Chile - Wratten, S. D.; Shields, M. W.; González-Chang, M. (Agro Sur, 2019)
A global perspective, why we need a greener agriculture? “I am a photosynthesis manager and an ecosystemservice provider”. This profound statement was made by a Swedish farmer some years ago (Wratten, 2018). Few farmers describe their occupation in this way. However, there is a major body of work giving substantial evidence that current high-input farming (Figure 1) has no future without changes to its approach (Pretty et al., 2018). One reason for this view is that agriculture is one of the main causes of climate disturbance, largely driven by changes in land-use practices (Bennetzen et al., 2016). The main consequence has been biodiversity loss (Sala et al., 2000). A very worrying example of this is ...